Concrete with high compression resistance and corrosion resistance and preparation method thereof
By using modified hydrophobic polyvinyl alcohol fibers and modified polymer emulsions in concrete, a uniform messy support system is formed, which solves the shortcomings of existing concrete in terms of compression and corrosion resistance, and achieves high compression and corrosion resistance. and flame retardant comprehensive performance.
Patent Information
- Application Number
- CN202411333809.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing concrete has shortcomings in its compression and corrosion resistance, and it is difficult to achieve high compression, corrosion and flame retardant effects at the same time.
Modified hydrophobic polyvinyl alcohol fiber and modified polymer emulsion are mixed and filled to form a uniform messy support system, improving the mechanical strength and corrosion resistance of concrete, and enhancing flame retardant by introducing sulfonic acid groups and silicon elements. performance.
It significantly improves the compressive strength and corrosion resistance of concrete, and at the same time achieves flame retardant effect, meeting the comprehensive performance requirements of high compression, corrosion resistance and flame retardant.
Smart Images

Figure BDA0005057725790000071 
Figure BDA0005057725790000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete, in particular to a high-compression-resistant and corrosion-resistant concrete and a preparation method thereof. Background Art
[0002] Concrete is widely used in various buildings due to its high compressive strength, low price, and good bonding with steel bars. However, due to the material properties of concrete itself, it has problems such as high brittleness and poor durability, making it difficult to adapt to modern engineering requirements, so concrete needs to be modified. Many test results show that the addition of PVA fibers can enhance the corrosion resistance of concrete used in roadbed engineering in a chloride ion environment and effectively extend the service life of concrete structures, but there is still room for further optimization of the salt corrosion resistance of fiber-reinforced concrete.
[0003] At the same time, polymer-modified cement concrete, as a new trend in cement concrete, is a composite of ordinary cement concrete and organic polymer materials, or adding a small amount of organic polymer materials of different types, properties and quantities to ordinary cement concrete, which can effectively improve the performance of concrete and even give cement concrete new properties. Because the long molecular chain structure of organic polymers and the self-rotation of the key nodes or segments in the macromolecules determine that they have different properties from inorganic non-metallic materials. Therefore, adding a small amount of organic polymers to ordinary cement concrete can not only make the concrete have a high density, but also will not increase the brittleness of the concrete, thereby further broadening the application field of concrete. However, there is little research on polymer-modified concrete at present, and most related studies only show that the mechanical properties are enhanced, and it is impossible to achieve the effects of compression resistance, corrosion resistance and flame retardancy at the same time. Summary of the invention
[0004] The purpose of the present invention is to provide a high compression and corrosion resistance concrete and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a high compressive and corrosion-resistant concrete, which is prepared by mixing modified hydrophobic polyvinyl alcohol fibers and modified polymer emulsion and filling concrete.
[0006] Furthermore, the modified hydrophobic polyvinyl alcohol fiber is prepared by copolymerizing modified polyvinyl alcohol, sodium styrene sulfonate and allylmethyldimethoxysilane.
[0007] Furthermore, the modified polyvinyl alcohol is prepared by grafting undecylenic alcohol onto the surface of polyvinyl alcohol under acidic conditions.
[0008] Furthermore, the modified polymer emulsion is prepared by the polymerization reaction of allyl trimethyl ammonium chloride and allyl alcohol glycidyl ether with styrene acrylate.
[0009] Furthermore, a method for preparing high compressive and corrosion resistant concrete comprises the following preparation steps:
[0010] (1) Dissolve 6 to 14 parts of polyvinyl alcohol in 60 to 112 parts of deionized water, add 15 to 31 parts of undecenal, heat to 55 to 75° C., stir at 70 rpm for 10 to 20 min, adjust the pH to 3.5 to 4.5 with dilute hydrochloric acid, continue stirring for 50 to 70 min, cool to 25° C., add 97 to 163 parts of ethanol, stir at 100 rpm for 20 to 40 min, filter out the solid, wash with ethanol three times, and dry in an oven at 40 to 50° C. for 10 to 16 h to obtain modified polyvinyl alcohol;
[0011] (2) Under nitrogen protection, 4 to 8 parts of modified polyvinyl alcohol, 3 to 7 parts of sodium styrene sulfonate, and 56 to 120 parts of dimethylformamide were mixed uniformly at 35° C., 2 to 6 parts of allylmethyldimethoxysilane and 0.1 to 0.3 parts of azobisisobutyronitrile were added dropwise, the temperature was raised to 60 to 70° C., and the mixture was stirred at 80 rpm for 1 to 2 h. The pH was adjusted to 7 to 8 with an aqueous sodium hydroxide solution, the mixture was cooled to 25° C., 105 to 225 parts of ethanol were added, and the mixture was stirred at 120 rpm for 30 to 40 min. The solid was filtered and washed with ethanol three times, and dried in an oven at 40 to 50° C. for 8 to 16 h to obtain a modified hydrophobic polyvinyl alcohol;
[0012] (3) 77 to 125 parts of modified hydrophobic polyvinyl alcohol, 1 to 3 parts of nano-silicon dioxide with a particle size of 20 nm, and 2 to 4 parts of phthalate are uniformly mixed, and melt-spinned by spraying, with the spinning screw temperature of 280 to 290° C., the cooling air temperature of 19 to 23° C., the wind speed of 0.8 to 1.0 m / s, and the wind pressure of 500 to 700 Pa to obtain modified hydrophobic polyvinyl alcohol fiber;
[0013] (4) Under nitrogen protection, 114-208 parts of deionized water, 21-33 parts of allyl trimethyl ammonium chloride, 19-31 parts of allyl alcohol glycidyl ether, and 1-3 parts of Gemini emulsifier HL-03 were mixed uniformly, 36-48 parts of styrene and 32-44 parts of butyl acrylate were added, and the mixture was stirred at 240 rpm for 10-30 min, and 0.5-1.5 parts of azobisisobutyronitrile were added, the mixture was heated to 70-80° C., and stirred at 150 rpm for 4-6 h, and the mixture was cooled to 25° C., the solid was filtered, washed with deionized water for 3 times, and dried in an oven at 50-60° C. for 12-16 h to obtain a modified polymer emulsion;
[0014] (5) 5 to 9 parts of modified hydrophobic polyvinyl alcohol fibers, 3 to 5 parts of modified polymer emulsion, 10 to 20 parts of cement, 24 to 50 parts of crushed stone, 11 to 23 parts of aggregate, 5 to 9 parts of filler, and 6 to 10 parts of water are uniformly mixed to prepare high compressive and corrosion resistant concrete.
[0015] Furthermore, the model of the polyvinyl alcohol in step (1) is PVA-1788; and the concentration of the dilute hydrochloric acid is 1 mol / L.
[0016] Furthermore, the dropping rate in step (2) is 1 drop / s; and the concentration of the sodium hydroxide aqueous solution is 2 mol / L.
[0017] Furthermore, the cement in step (5) is any one of 32.5R, 42.5R, and 52.5R.
[0018] Furthermore, the aggregate in step (5) is recycled concrete or river sand with a particle size of 0.5 to 20 mm.
[0019] Furthermore, the filler in step (5) is a mixture of one or more of rice husk powder, slag, and fly ash.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0021] The present invention utilizes modified hydrophobic polyvinyl alcohol fibers to be evenly distributed inside the concrete to form a uniform random support system, so that microcracks formed in the initial stage of concrete hardening are blocked during the development process and are difficult to develop further. The modified polymer emulsion is mixed and filled in the concrete to achieve high compression resistance, corrosion resistance and flame retardancy.
[0022] Firstly, the modified hydrophobic polyvinyl alcohol fiber is grafted on the surface of polyvinyl alcohol by undecene aldehyde under acidic conditions, and a long carbon chain is introduced to improve the adhesion with concrete, and at the same time, the water absorption of concrete is reduced, the pore generation is reduced, and the entry of corrosive liquid is blocked, thereby improving the mechanical strength and corrosion resistance of concrete; then, the alkenyl in the grafted polyvinyl alcohol is polymerized with the unsaturated double bonds of sodium styrene sulfonate and allyl methyl dimethoxy silane to form a three-dimensional network structure, which significantly improves the overall mechanical strength and thermal stability; the sulfonic acid group introduced by sodium styrene sulfonate makes it impossible for concrete to undergo a replacement reaction with an acidic medium, thereby improving corrosion resistance. On this basis, during combustion, the sulfonate can decompose or volatilize some low-molecular substances, absorb heat, and reduce the surrounding temperature, thereby slowing down the decomposition and combustion rate of the material, and can also form a carbonized layer on the surface of the material to achieve flame retardant properties, assist the silicon element in allyl methyl dimethoxy silane, improve thermal stability, and increase the ignition point. During combustion, a glass-like covering layer is formed, which cooperates with the carbonized layer to isolate oxygen and combustibles, inhibit the combustion of flames, and further enhance the flame retardant effect.
[0023] Secondly, the modified polymer emulsion is prepared by the polymerization reaction of allyl trimethyl ammonium chloride and allyl alcohol glycidyl ether with styrene acrylate; a small amount of cations are introduced by allyl trimethyl ammonium chloride to react with anions in the concrete to slow down the corrosion rate, thereby achieving a corrosion-resistant effect; glycidyl ether is used as an auxiliary to increase the slump of concrete, improve the fluidity of concrete, reduce segregation and stratification, and thus improve the mechanical strength and durability of concrete. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0025] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the high compressive and corrosion resistant concrete prepared in the following examples are as follows:
[0026] Compressive strength and cracks: The same mass of the embodiment and the comparative example was made into a cube of 150 mm×150 mm×150 mm. After curing for 28 days, the compressive strength was tested according to GB / T 50081, and the surface of each group of samples was observed to see whether there were cracks.
[0027] Flame retardant grade: The same mass of the embodiment and the comparative example was made into a cube of 150 mm×150 mm×150 mm, and the fire retardant grade was tested according to the UL94 standard.
[0028] Anti-corrosion coefficient: The same mass of the embodiment and the comparative example was made into a cube of 150 mm×150 mm×150 mm, and tested according to GB / T 749-2008.
[0029] Example 1
[0030] (1) 6 parts of PVA-1788 were dissolved in 60 parts of deionized water, 15 parts of undecenal were added, the temperature was raised to 55°C, the mixture was stirred at 70 rpm for 10 min, the pH was adjusted to 3.5 with 1 mol / L dilute hydrochloric acid, the mixture was stirred for 50 min, the temperature was lowered to 25°C, 97 parts of ethanol were added, the mixture was stirred at 100 rpm for 20 min, the solid was filtered out, the solid was washed with ethanol three times, and the mixture was dried in an oven at 40°C for 10 h to obtain modified polyvinyl alcohol;
[0031] (2) Under nitrogen protection, 4 parts of modified polyvinyl alcohol, 3 parts of sodium styrene sulfonate, and 56 parts of dimethylformamide were mixed at 35° C., 2 parts of allylmethyldimethoxysilane and 0.1 parts of azobisisobutyronitrile were added dropwise at a rate of 1 drop / s, the temperature was raised to 60° C., and the mixture was stirred at 80 rpm for 1 h. The pH was adjusted to 7 with a 2 mol / L sodium hydroxide aqueous solution, the mixture was cooled to 25° C., 105 parts of ethanol were added, and the mixture was stirred at 120 rpm for 30 min. The solid was filtered and washed with ethanol 3 times, and dried in an oven at 40° C. for 8 h to obtain a modified hydrophobic polyvinyl alcohol;
[0032] (3) 77 parts of modified hydrophobic polyvinyl alcohol, 1 part of nano-silicon dioxide with a particle size of 20 nm, and 2 parts of phthalate are mixed uniformly, and melt-spinned at a spinning screw temperature of 280° C., a cooling air temperature of 19° C., a wind speed of 0.8 m / s, and a wind pressure of 500 Pa to obtain modified hydrophobic polyvinyl alcohol fibers;
[0033] (4) Under nitrogen protection, 114 parts of deionized water, 21 parts of allyl trimethyl ammonium chloride, 19 parts of allyl alcohol glycidyl ether, and 1 part of Gemini emulsifier HL-03 were mixed evenly, 36 parts of styrene and 32 parts of butyl acrylate were added, and the mixture was stirred at 240 rpm for 10 min, 0.5 parts of azobisisobutyronitrile was added, the temperature was raised to 70° C., and the mixture was stirred at 150 rpm for 4 h. The mixture was cooled to 25° C., the solid was filtered, washed with deionized water 3 times, and dried in an oven at 50° C. for 12 h to obtain a modified polymer emulsion;
[0034] (5) 5 parts of modified hydrophobic polyvinyl alcohol fiber, 3 parts of modified polymer emulsion, 10 parts of 32.5R cement, 24 parts of crushed stone, 11 parts of recycled concrete aggregate with a particle size of 0.5 mm, 5 parts of rice husk powder, and 6 parts of water were mixed evenly to prepare high compressive and corrosion-resistant concrete.
[0035] Example 2
[0036] (1) Dissolve 10 parts of PVA-1788 in 86 parts of deionized water, add 23 parts of undecenal, heat to 65°C, stir at 70 rpm for 15 min, adjust the pH to 4.0 with 1 mol / L dilute hydrochloric acid, continue stirring for 60 min, cool to 25°C, add 130 parts of ethanol, stir at 100 rpm for 30 min, filter out the solid, wash with ethanol three times, and dry in an oven at 45°C for 13 h to obtain modified polyvinyl alcohol;
[0037] (2) Under nitrogen protection, 6 parts of modified polyvinyl alcohol, 5 parts of sodium styrene sulfonate, and 88 parts of dimethylformamide were mixed at 35°C, 4 parts of allylmethyldimethoxysilane and 0.2 parts of azobisisobutyronitrile were added at a rate of 1 drop / s, the temperature was raised to 65°C, and the mixture was stirred at 80 rpm for 1.5 h. The pH was adjusted to 7.5 with a 2 mol / L sodium hydroxide aqueous solution, the mixture was cooled to 25°C, 165 parts of ethanol was added, and the mixture was stirred at 120 rpm for 35 min. The solid was filtered and washed with ethanol three times, and dried in an oven at 45°C for 12 h to obtain a modified hydrophobic polyvinyl alcohol;
[0038] (3) 101 parts of modified hydrophobic polyvinyl alcohol, 2 parts of nano-silicon dioxide with a particle size of 20 nm, and 3 parts of phthalate are mixed uniformly, and melt-spinned by spraying, with the spinning screw temperature of 285° C., the cooling air temperature of 21° C., the wind speed of 0.9 m / s, and the wind pressure of 600 Pa to obtain modified hydrophobic polyvinyl alcohol fiber;
[0039] (4) Under nitrogen protection, 161 parts of deionized water, 27 parts of allyl trimethyl ammonium chloride, 25 parts of allyl alcohol glycidyl ether, and 2 parts of Gemini emulsifier HL-03 were mixed evenly, 42 parts of styrene and 38 parts of butyl acrylate were added, and the mixture was stirred at 240 rpm for 20 min. 1.0 part of azobisisobutyronitrile was added, the temperature was raised to 75° C., and the mixture was stirred at 150 rpm for 5 h. The mixture was cooled to 25° C., the solid was filtered, washed with deionized water for 3 times, and dried in an oven at 55° C. for 14 h to obtain a modified polymer emulsion;
[0040] (5) 7 parts of modified hydrophobic polyvinyl alcohol fiber, 4 parts of modified polymer emulsion, 15 parts of 42.5R cement, 37 parts of crushed stone, 17 parts of river sand with a particle size of 10.3 mm, 7 parts of slag, and 8 parts of water were mixed evenly to prepare high compressive and corrosion-resistant concrete.
[0041] Example 3
[0042] (1) 14 parts of PVA-1788 were dissolved in 112 parts of deionized water, 31 parts of undecenal were added, the temperature was raised to 75°C, the mixture was stirred at 70 rpm for 20 min, the pH was adjusted to 4.5 with 1 mol / L dilute hydrochloric acid, the mixture was stirred for 70 min, the temperature was lowered to 25°C, 163 parts of ethanol were added, the mixture was stirred at 100 rpm for 40 min, the solid was filtered, the solid was washed with ethanol three times, and the mixture was dried in an oven at 50°C for 16 h to obtain modified polyvinyl alcohol;
[0043] (2) Under nitrogen protection, 8 parts of modified polyvinyl alcohol, 7 parts of sodium styrene sulfonate, and 120 parts of dimethylformamide were mixed at 35° C., 6 parts of allylmethyldimethoxysilane and 0.3 parts of azobisisobutyronitrile were added dropwise at a rate of 1 drop / s, the temperature was raised to 70° C., and the mixture was stirred at 80 rpm for 2 h. The pH was adjusted to 8 with a 2 mol / L sodium hydroxide aqueous solution, the mixture was cooled to 25° C., 225 parts of ethanol were added, and the mixture was stirred at 120 rpm for 40 min. The solid was filtered and washed with ethanol three times, and dried in an oven at 50° C. for 16 h to obtain a modified hydrophobic polyvinyl alcohol;
[0044] (3) 125 parts of modified hydrophobic polyvinyl alcohol, 3 parts of nano-silicon dioxide with a particle size of 20 nm, and 4 parts of phthalate were mixed uniformly, and melt-spinned at a spinning screw temperature of 290° C., a cooling air temperature of 23° C., a wind speed of 1.0 m / s, and a wind pressure of 700 Pa to obtain modified hydrophobic polyvinyl alcohol fibers;
[0045] (4) Under nitrogen protection, 208 parts of deionized water, 33 parts of allyl trimethyl ammonium chloride, 31 parts of allyl alcohol glycidyl ether, and 3 parts of Gemini emulsifier HL-03 were mixed evenly, 48 parts of styrene and 44 parts of butyl acrylate were added, and the mixture was stirred at 240 rpm for 30 min. 1.5 parts of azobisisobutyronitrile was added, the temperature was raised to 80° C., and the mixture was stirred at 150 rpm for 6 h. The mixture was cooled to 25° C., the solid was filtered, washed with deionized water for 3 times, and dried in an oven at 60° C. for 16 h to obtain a modified polymer emulsion;
[0046] (5) 9 parts of modified hydrophobic polyvinyl alcohol fiber, 5 parts of modified polymer emulsion, 20 parts of 52.5R cement, 50 parts of crushed stone, 23 parts of recycled concrete aggregate with a particle size of 20 mm, 9 parts of fly ash, and 10 parts of water were mixed evenly to prepare high compressive and corrosion-resistant concrete.
[0047] Comparative Example 1
[0048] The difference between Comparative Example 1 and Example 2 is that there is no step (1), and step (2) is changed to: under nitrogen protection, 6 parts of PVA-1788, 5 parts of sodium styrene sulfonate, and 88 parts of dimethylformamide are mixed uniformly at 35° C., 4 parts of allylmethyldimethoxysilane and 0.2 parts of azobisisobutyronitrile are added dropwise at a rate of 1 drop / s, the temperature is raised to 65° C., stirred at 80 rpm for 1.5 h, the pH is adjusted to 7.5 with a 2 mol / L sodium hydroxide aqueous solution, cooled to 25° C., 165 parts of ethanol are added, stirred at 120 rpm for 35 min, the solid is filtered, washed with ethanol 3 times, and dried in an oven at 45° C. for 12 h to obtain modified hydrophobic polyvinyl alcohol. The remaining steps are the same as those in Example 2.
[0049] Comparative Example 2
[0050] The difference between Comparative Example 2 and Example 2 is that step (2) is different. Step (2) is changed to: under nitrogen protection, 6 parts of modified polyvinyl alcohol and 88 parts of dimethylformamide are mixed uniformly at 35° C., 4 parts of allylmethyldimethoxysilane and 0.2 parts of azobisisobutyronitrile are added dropwise at a rate of 1 drop / s, the temperature is raised to 65° C., stirred at 80 rpm for 1.5 h, the pH is adjusted to 7.5 with a 2 mol / L sodium hydroxide aqueous solution, cooled to 25° C., 165 parts of ethanol are added, stirred at 120 rpm for 35 min, the solid is filtered, washed with ethanol 3 times, and dried in an oven at 45° C. for 12 h to obtain modified hydrophobic polyvinyl alcohol. The remaining steps are the same as those in Example 2.
[0051] Comparative Example 3
[0052] The difference between Comparative Example 3 and Example 2 is that step (2) is different. Step (2) is changed to: under nitrogen protection, 6 parts of modified polyvinyl alcohol, 5 parts of sodium styrene sulfonate, and 88 parts of dimethylformamide are mixed uniformly at 35° C., 0.2 parts of azobisisobutyronitrile are added dropwise at a rate of 1 drop / s, the temperature is raised to 65° C., stirred at 80 rpm for 1.5 h, the pH is adjusted to 7.5 with a 2 mol / L sodium hydroxide aqueous solution, cooled to 25° C., 165 parts of ethanol are added, stirred at 120 rpm for 35 min, the solid is filtered, washed with ethanol 3 times, and dried in an oven at 45° C. for 12 h to obtain modified hydrophobic polyvinyl alcohol. The remaining steps are the same as those in Example 2.
[0053] Comparative Example 4
[0054] The difference between Comparative Example 4 and Example 2 is that step (4) is different. Step (4) is changed to: under nitrogen protection, 161 parts of deionized water, 25 parts of allyl alcohol glycidyl ether, and 2 parts of Gemini emulsifier HL-03 are mixed uniformly, 42 parts of styrene and 38 parts of butyl acrylate are added, and the mixture is stirred at 240 rpm for 20 min, 1.0 part of azobisisobutyronitrile is added, the mixture is heated to 75° C., stirred at 150 rpm for 5 h, cooled to 25° C., the solid is filtered, washed with deionized water 3 times, and dried in an oven at 55° C. for 14 h to obtain a modified polymer emulsion. The remaining steps are the same as those in Example 2.
[0055] Comparative Example 5
[0056] The difference between Comparative Example 5 and Example 2 is that step (4) is different. Step (4) is changed to: under nitrogen protection, 161 parts of deionized water, 27 parts of allyltrimethylammonium chloride, and 2 parts of Gemini emulsifier HL-03 are mixed uniformly, 42 parts of styrene and 38 parts of butyl acrylate are added, and the mixture is stirred at 240 rpm for 20 min, 1.0 part of azobisisobutyronitrile is added, the mixture is heated to 75° C., stirred at 150 rpm for 5 h, cooled to 25° C., the solid is filtered, washed with deionized water 3 times, and dried in an oven at 55° C. for 14 h to obtain a modified polymer emulsion. The remaining steps are the same as those in Example 2.
[0057] Effect example
[0058] Table 1 below shows the performance analysis results of the high compression and corrosion resistant concrete using Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0059] Table 1
[0060]
[0061]
[0062] From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 1, it can be found that by grafting undecylenic aldehyde on the surface of polyvinyl alcohol under acidic conditions, a long carbon chain is introduced, the adhesion between the concrete and the concrete is improved, and at the same time, the water absorption of the concrete is reduced, the generation of pores is reduced, and the entry of corrosive liquids is blocked, thereby significantly improving the compressive strength and corrosion resistance of the concrete; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 2, it can be found that the sulfonic acid group introduced by sodium styrene sulfonate prevents the concrete from undergoing a replacement reaction with an acidic medium, thereby improving the corrosion resistance. At the same time, during combustion, the sulfonate can decompose or volatilize some low-molecular substances, absorb heat, reduce the ambient temperature, slow down the decomposition and combustion rate of the material, and form a carbonized layer on the surface of the material to achieve flame retardant properties .... By comparing the experimental data of Comparative Example 3, it can be found that the silicon element in allylmethyldimethoxysilane can improve thermal stability, increase the ignition point, form a glass-like covering layer during combustion, and cooperate with the carbonized layer formed by sodium sulfonate to isolate oxygen and combustibles, inhibit the combustion of flames, and significantly enhance the flame retardant effect; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 4, it can be found that a small amount of cations are introduced by using allyltrimethylammonium chloride to react with anions in concrete to slow down the corrosion rate, thereby achieving a corrosion-resistant effect; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 5, it can be found that the addition of allyl alcohol glycidyl ether increases the slump of concrete, improves the fluidity of concrete, reduces segregation and stratification, and improves the mechanical strength and durability of concrete.
[0063] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A high compressive and corrosion resistant concrete, characterized in that: The high compression and corrosion resistance concrete is prepared by mixing modified hydrophobic polyvinyl alcohol fibers and modified polymer emulsion and filling the concrete.
2. The high compressive and corrosion resistant concrete according to claim 1, characterized in that: The modified hydrophobic polyvinyl alcohol fiber is prepared by copolymerizing modified polyvinyl alcohol, sodium styrene sulfonate and allylmethyldimethoxysilane.
3. The high compressive and corrosion resistant concrete according to claim 2, characterized in that: The modified polyvinyl alcohol is prepared by grafting undecenyl alcohol on the surface of polyvinyl alcohol under acidic conditions.
4. The high compressive and corrosion resistant concrete according to claim 1, characterized in that: The modified polymer emulsion is prepared by the polymerization reaction of allyl trimethyl ammonium chloride and allyl alcohol glycidyl ether with styrene acrylate.
5. A method for preparing high compressive and corrosion resistant concrete, characterized in that: The method comprises the following preparation steps: (1) Dissolve 6 to 14 parts of polyvinyl alcohol in 60 to 112 parts of deionized water, add 15 to 31 parts of undecenal, heat to 55 to 75° C., stir at 70 rpm for 10 to 20 min, adjust the pH to 3.5 to 4.5 with dilute hydrochloric acid, continue stirring for 50 to 70 min, cool to 25° C., add 97 to 163 parts of ethanol, stir at 100 rpm for 20 to 40 min, filter out the solid, wash with ethanol three times, and dry in an oven at 40 to 50° C. for 10 to 16 h to obtain modified polyvinyl alcohol; (2) Under nitrogen protection, 4 to 8 parts of modified polyvinyl alcohol, 3 to 7 parts of sodium styrene sulfonate, and 56 to 120 parts of dimethylformamide were mixed uniformly at 35° C., 2 to 6 parts of allylmethyldimethoxysilane and 0.1 to 0.3 parts of azobisisobutyronitrile were added dropwise, the temperature was raised to 60 to 70° C., and the mixture was stirred at 80 rpm for 1 to 2 h. The pH was adjusted to 7 to 8 with an aqueous sodium hydroxide solution, the mixture was cooled to 25° C., 105 to 225 parts of ethanol were added, and the mixture was stirred at 120 rpm for 30 to 40 min. The solid was filtered and washed with ethanol three times, and dried in an oven at 40 to 50° C. for 8 to 16 h to obtain a modified hydrophobic polyvinyl alcohol; (3) 77 to 125 parts of modified hydrophobic polyvinyl alcohol, 1 to 3 parts of nano-silicon dioxide with a particle size of 20 nm, and 2 to 4 parts of phthalate are uniformly mixed, and melt-spinned by spraying, with the spinning screw temperature of 280 to 290° C., the cooling air temperature of 19 to 23° C., the wind speed of 0.8 to 1.0 m / s, and the wind pressure of 500 to 700 Pa to obtain modified hydrophobic polyvinyl alcohol fiber; (4) Under nitrogen protection, 114-208 parts of deionized water, 21-33 parts of allyl trimethyl ammonium chloride, 19-31 parts of allyl alcohol glycidyl ether, and 1-3 parts of Gemini emulsifier HL-03 were mixed uniformly, 36-48 parts of styrene and 32-44 parts of butyl acrylate were added, and the mixture was stirred at 240 rpm for 10-30 min, and 0.5-1.5 parts of azobisisobutyronitrile were added, the mixture was heated to 70-80° C., and stirred at 150 rpm for 4-6 h, and the mixture was cooled to 25° C., the solid was filtered, washed with deionized water for 3 times, and dried in an oven at 50-60° C. for 12-16 h to obtain a modified polymer emulsion; (5) 5 to 9 parts of modified hydrophobic polyvinyl alcohol fibers, 3 to 5 parts of modified polymer emulsion, 10 to 20 parts of cement, 24 to 50 parts of crushed stone, 11 to 23 parts of aggregate, 5 to 9 parts of filler, and 6 to 10 parts of water are uniformly mixed to prepare high compressive and corrosion resistant concrete.
6. The method for preparing high compressive and corrosion resistant concrete according to claim 5, characterized in that: The model of the polyvinyl alcohol in step (1) is PVA-1788; the concentration of the dilute hydrochloric acid is 1 mol / L.
7. The method for preparing high compressive and corrosion resistant concrete according to claim 5, characterized in that: The dropping rate in step (2) is 1 drop / s; and the concentration of the sodium hydroxide aqueous solution is 2 mol / L.
8. The method for preparing high compressive and corrosion resistant concrete according to claim 5, characterized in that: The cement in step (5) is any one of 32.5R, 42.5R and 52.5R.
9. The method for preparing high compressive and corrosion resistant concrete according to claim 5, characterized in that: The aggregate in step (5) is recycled concrete or river sand with a particle size of 0.5 to 20 mm.
10. The method for preparing high compressive and corrosion resistant concrete according to claim 5, characterized in that: The filler in step (5) is a mixture of one or more of rice husk powder, slag and fly ash.
Citation Information
Patent Citations
Preparation method of fiber-reinforced high-damping polymer concrete
CN106242442A
Glass-fiber-reinforced flame-retardant polycarbonate composite material, and preparation method and applications thereof
CN110157174A
Fiber reinforced concrete raw material, fiber reinforced concrete and preparation method and application thereof
CN110330273A
Preparation method of building composite waterproof material
CN110482951A
High-cohesiveness fiber reinforced concrete and processing technology thereof
CN111807781A